Influence of landscape structure on movement behavior and habitat use by red flour beetle (Tribolium castaneum) - Romero, Susan (Kansas State University, 2007)
Theoretical and empirical ecological research has emphasized the need for understanding how animals perceive and respond to landscape structure and the importance of integrating both behavioral and landscape approaches when studying movement behavior. Knowledge of insect movement behavior is essential for understanding and modeling dispersal and population structure and developing biologically-based integrated pest management programs. My dissertation research addresses questions concerning how insects respond to landscape structure by examining movement behavior of an important stored-product pest, red flour beetle (Tribolium castaneum), in experimental landscapes. Results show that beetles modify movement behavior depending on landscape structure. Edge effects and interpatch distances may influence landscape viscosity, or the degree to which landscape structure facilitates or impedes movement, resulting in significant differences in velocity and tortuosity (amount of turning) of movement pathways, as well as retention time in landscapes with different levels of habitat abundance and aggregation. Perceptual range, or the distance from which habitat is detected, appears to be limited while beetles are moving in a landscape as they did not respond to a flour resource before physical encounter. Beetles showed differential responses to patches with various characteristics, entering covered patches more quickly than uncovered patches with more resource or the same amount of resource. Permeability of patches changed with subsequent encounters suggesting that full evaluation of patch quality may only occur after entering a patch. Beetles responded to landscape structure differently depending on the activity in which they were engaged. Distribution of movement pathways was similar to that of the habitat, but distribution of oviposition sites were significantly more aggregated than pathways and habitat. Oviposition site choice may be influenced by a complex set of factors which include previous visitation, amount of resource, travel costs, and edge effects. Insights were gained concerning how red flour beetle perceives resources, modifies search strategies, responds to boundaries, and chooses reproductive sites in patchy landscapes. This research provides new information regarding how red flour beetle interacts with landscape structure that has implications in the areas of behavioral and landscape ecology and applications in stored-product insect ecology.
Keywords: Insect movement behavior; Landscape structure; Tribolium castaneum; Biology, Ecology (0329); Biology, Entomology (0353)